Evaluation of growth and yield of cowpea (Vigna unguiculata L.Walp) cultivars and sorghum (Sorghum bicolor L. Moench) with their competitive behavior in cowpea-sorghum intercropping. - Afe, A. I.; Nuruden, K.; Yaman, U. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
The need to increase cowpea production to solve the menace of malnutrition is a global challenge and land limitations have also made intercropping indispensable. Field trials were carried out at the Teaching and Research Farm, Kwara State University, Malete, and National Centre for Agricultural Mechanization (NCAM) Idofian to evaluate the growth and yield of cowpea cultivars and sorghum with their competitive behavior in cowpea-sorghum intercropping. Five cultivars of cowpea (IITA-256, IITA-277, VITAL-5, IT98K-491-4, and IITA-288) were intercropped with sorghum. Sole crops were included in the treatments as a check. The treatments were arranged in a Randomized Complete Block Design and replicated three times. Among the sole, vital-5 cultivar had the highest number of branches and pods per plant and more seeds per pod compared to other cultivars. The cultivar also recorded the highest grain yield 591.30 kg/ha and 530.00 kg/ha respectively, for Malete and NCAM at the sole. At the intercrop, IITA-288 significantly had the least number of branches per plant and took longer days to attain flowering compared to other cultivars. The lowest grain yield at the intercrop was also obtained with this cultivar. Sorghum intercropped with cowpea cultivar IITA-288 was at par with the sole sorghum in all the parameters. The least grain yield of sorghum at the intercrop was obtained in sorghum intercropping with IITA-256 cowpea cultivar. The maximum Land Equivalent Ratio (LER), and Land Equivalent Coefficient (LEC), was obtained with the Vital-5 cultivar. Regardless of location, the competitive ratio (CR) values for IITA-256, IITA-277, and Vital-5 cowpea cultivars were higher than sorghum. The aggressivisity, (A) for these cultivars were also positive for cowpea and negative for sorghum. Although, all the cowpea cultivars demonstrated intercropping advantages in efficient utilization of natural resources intercropping with the Vital-5 cowpea cultivar was superior and could be adopted by the farmer.